Influence of Plasma-Isolated Anthocyanins and Their Metabolites on Cancer Cell Migration (HT-29 and Caco-2) In Vitro: Results of the ATTACH Study - Inken Behrendt; Isabella Röder; Frank Will; Hamza Mostafa; Raúl Gonzalez-Dominguez; Tomás Meroño; Cristina Andres-Lacueva; Mathias Fasshauer; Silvia Rudloff; Sabine Kuntz (MDPI AG, 2022)
Cancer mortality is mainly due to metastasis. Therefore, searching for new therapeutic agents suppressing cancer cell migration is crucial. Data from human studies regarding effects of anthocyanins on cancer progression, however, are scarce and it is unclear whether physiological concentrations of anthocyanins and their metabolites reduce cancer cell migration in vivo. In addition, interactions with chemotherapeutics like 5-fluorouracil (5-FU) are largely unknown. Thus, we combined a placebo-controlled, double-blinded, cross-over study with in vitro migration studies of colon cancer cell lines to examine the anti-migratory effects of plasma-isolated anthocyanins and their metabolites (PAM). Healthy volunteers (n = 35) daily consumed 0.33 L of an anthocyanin-rich grape/bilberry juice and an anthocyanin-depleted placebo juice for 28 days. PAM were isolated before and after intervention by solid-phase extraction. HT-29 and Caco-2 cells were incubated with PAM in a Boyden chamber. Migration of HT-29 cells was significantly inhibited by PAM from juice but not from placebo. In contrast, Caco-2 migration was not affected. Co-incubation with 5-FU and pooled PAM from volunteers (n = 10), which most effectively inhibited HT-29 migration, further reduced HT-29 migration in comparison to 5-FU alone. Therefore, PAM at physiological concentrations impairs colon cancer cell migration and may support the effectiveness of chemotherapeutics.